2018
DOI: 10.1051/matecconf/201816203004
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of reusing Al-Machraya River for feeding Hawizeh marsh

Abstract: Al Machraya River was considered as one of the water feeders of Hawizeh Marsh. In 1986, the outlet of this river into the marsh was blocked and the river was used as a main channel for the East Tigris Irrigation Project near Kalat Salih. This causes significant decrease in the available water supply sources, deterioration in the water quality distribution patterns and increasing the stagnation areas within the marsh. This research aims to study the possibility of reusing this river for feeding Hawizeh Marsh. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Literature shows that considerable research work was conducted on marsh restoration (Curtis et al, 2005 ; DAI, 2006 ; Iraqi Ministries of Environment et al 2006 ; CRIM 2007 unpublished report; CRIM 2008 unpublished report; Riyadh et al, 2008 ; CRIM 2009a unpublished report; CRIM 2009b unpublished report; Al-Saboonchi et al, 2011 ; Al-Ameri and Jassim ( 2011 ); Al-Ansari & Knutsson, 2011 ; Al-Ansari et al, 2012 ; Muhannad et al, 2013 ; Al-Gburi et al, 2017 ; Al-Khafaji et al, 2018 ; Al-Khafaji et al, 2021 ; Bayda et al, 2022 ). Furthermore, various studies have shown that Iraq is one of the most vulnerable countries to climate change and its water resources begin significantly impacted, such as Chenoweth et al ( 2011 ), Abbas et al ( 2016 ), Abbas et al ( 2017 ), Awchi and Kalyana ( 2017 ), Al-Khafaji and Al-Chalabi ( 2019 ), Constantinidou et al ( 2019 ), and Saeed et al ( 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that considerable research work was conducted on marsh restoration (Curtis et al, 2005 ; DAI, 2006 ; Iraqi Ministries of Environment et al 2006 ; CRIM 2007 unpublished report; CRIM 2008 unpublished report; Riyadh et al, 2008 ; CRIM 2009a unpublished report; CRIM 2009b unpublished report; Al-Saboonchi et al, 2011 ; Al-Ameri and Jassim ( 2011 ); Al-Ansari & Knutsson, 2011 ; Al-Ansari et al, 2012 ; Muhannad et al, 2013 ; Al-Gburi et al, 2017 ; Al-Khafaji et al, 2018 ; Al-Khafaji et al, 2021 ; Bayda et al, 2022 ). Furthermore, various studies have shown that Iraq is one of the most vulnerable countries to climate change and its water resources begin significantly impacted, such as Chenoweth et al ( 2011 ), Abbas et al ( 2016 ), Abbas et al ( 2017 ), Awchi and Kalyana ( 2017 ), Al-Khafaji and Al-Chalabi ( 2019 ), Constantinidou et al ( 2019 ), and Saeed et al ( 2021 ).…”
Section: Introductionmentioning
confidence: 99%